Professional and Elite Young Soccer Players: Differences in Functional Movement ScreenTM Values - Italo Sannicandro; Giacomo Cofano; Rosario D'Onofrio; Andrea Piccinno (Physical Education and Sports, 2023)
Background: Soccer is a sport that requires very complex movements performed at high speeds: running, jumping, decelerating, changing direction or running direction, and kicking are complex movements that require high control and significant joint stability at all ages. Control of the body and individual body districts becomes important for both performance and injury prevention.